Medical Cannabis: Modeling a Destigmatization Process for its Candidacy to Become a Pharmaceutical Brand - Ntais, Christos; Suvatjis, Jean; Melanthiou, Yioula (My University, 2023)
Purpose: This paper discusses an investigation of medical cannabis in an attempt to explore opportunities to liberate the product from its stigmatization and to identify possible routes for its candidacy to become a medical brand. It is believed that this is feasible with the contribution of social marketing. We present a conceptual model for medical cannabis destigmatization and justify the contribution of social marketing, as a bridge to attain a consensus within the opposing parties and clear the fog around the identity of medical cannabis. Design/methodology/approach: A literature review produced a pool of pertinent data associated with medical cannabis and its destigmatization process through social marketing. Findings: Data was grouped into two categories: (a) medical cannabis stigmatization and (b) social marketing as a tool to reduce stigma. Practical implications: Following the literature review, we were able to construct a Tri-stage model for destigmatizing medical cannabis and strategizing its future as a medical brand. Originality/value: The Tri-stage model will initiate discussions since it is the first to attempt the destigmatization of medical cannabis. We also emphasize and justify the contribution of social marketing acting as an ambassadorial agent to attain a consensus and to acquit medical cannabis, unfolding its real potential in medicine.
Keywords: Medical cannabis; stigmatization/destigmatization; social marketing